Investigation of resonant phenomena in a locomotive wheelset on the basis of calculation of natural frequencies and modes of their oscillations on finite element models - V. S. Kossov; E. S. Ogan’Yan; M. N. Ovechnikov; G. M. Volokhov; A. L. Protopopov; M. V. Timakov (Вестник Научно-исследовательского института железнодорожного транспорта)
From the practice of engineering design it is known that in the development of mechanical systems, the operation of which is certainly not based on the phenomena of resonance, self-synchronization, etc., one should be wary of the proximity of the frequencies of free oscillations in such mechanical systems in different forms. Transient processes are dangerous due to the excitation of significant quantities of mechanical stresses and their damage to structures before destruction. This effect can also be appeared in wheel pairs (WS) of locomotives during operation. On the finite element model (FE) of the electric locomotive wheelset, calculations of natural frequencies and vibration modes are performed, the case of torsional oscillation frequencies with the participation of the electric drive gear and bending (saddle-shaped) oscillations of the running wheels is demonstrated, which can accelerate the processes of origin and development in its fatigue cracks. Paper discusses methodical issues of performing such calculations, problems of assessing the degree of danger of proximity of vibration frequencies of structural elements. The prototype of the finite-element model considered in the article was the WS of a locomotive with an asynchronous transmission, a one-way reducer and a composite retaining wheel. Methodical issues of performing such calculations, problems of assessing the degree of danger of proximity of vibration frequencies of structural elements are discussed. The results of calculations in combination with their visualization give a fairly complete idea of the behavior of the wheelset in the traction drive, while allowing studying the stress-strain state of its parts, and also providing an opportunity to identify the damaged elements and zones. It is highly advisable to carry out similar studies on virtual models when analyzing the operation of locomotive structures and assemblies under extreme operating conditions (for example, in case of boxing), which is not practicable or dangerous by experimental methods. It is possible, as shown, and it is necessary at the design stage of the WS to conduct its frequency analysis in the manner described in the article and, based on its results, perform a resonant detuning in a constructive or software way in the frequency range of the modulation of the operation of an asynchronous drive. To this end, by analogy with the AAR S-669 standard (USA), it is necessary to develop a domestic regulatory document for the projected locomotives with an asynchronous drive.